Rehabilitation of ocular defects: Custom made and modified stock eye prostheses - Amaey A Parekh; Shailesh Bhalerao (Wolters Kluwer Medknow Publications, 2016)
Physical defects that compromise appearance or function prevent an individual from leading a normal life. The loss of eye is a visible facial defect and often undermines the patient's confidence. Prosthetic rehabilitation of ocular defect should be done as soon as possible for physical as well as psychological healing. This paper describes two case reports detailing alternative procedures for prosthetic rehabilitation of ocular defects. The article also discusses the most economical and effective esthetic treatment available for ocular defects as applicable in the Indian scenario. It describes the fabrication of a custom ocular prosthesis and modified stock ocular prosthesis and the differences in methods of fabrication and outcomes. In addition, use of Leudde's exopthalmometer for easier measurements is explained.